Pengaruh Stres Kerja dan Lingkungan Kerja Non Fisik terhadap Turnover Intention Melalui Kepuasan Kerja Karyawan pada Jalur Nugraha Ekakurir (JNE) Kantor Cabang Utama Jember - Diah Ayu Wulandari (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of work stress and non-physical work environment on turnover intention through job satisfaction among employees of Jalur Nugraha Ekakurir (JNE) Main Branch Office in Jember. Human resources are an essential asset that must be well managed to maintain performance and reduce turnover rates. However, JNE has experienced a relatively high level of turnover, particularly among courier employees, which is influenced by high work stress and an unsupportive non-physical work environment. This research employs an explanatory approach with 104 respondents selected using a saturated sampling technique. Data were collected through questionnaires and interviews, and analyzed using the Partial Least Square (PLS) method. The results indicate that work stress has a negative effect on job satisfaction and a positive effect on turnover intention, while the non-physical work environment has a positive effect on job satisfaction and a negative effect on turnover intention. Job satisfaction negatively affects turnover intention. However, job satisfaction does not significantly mediate the effect of work stress or the non-physical work environment, as the direct effects among variables are more dominant. Therefore, the mediation role of job satisfaction in this relationship is considered unnecessary keluarga tentang kontrasepsi pasca persalinan di wilayah kerja Puskesmas Kalisat perlu ditingkatkan. Hal ini dapat dilakukan dengan metode role playing terkait manfaat dari penggunaan kontrasepsi pasca persalinan. Tidak hanya itu, kader posyandu juga diharapkan untuk memperdalam pengetahuan terkait kontrasepsi pasca persalinan
Reap;oud Repository February 2026_Hasyim
Keywords: work stress; non-physical work environment; job satisfaction; turnover intention